Importance of independence in ribozyme reactions: kinetic behavior of trimmed and of simply connected multiple ribozymes with potential activity against human immunodeficiency virus. - Ohkawa, J (1993)
The kinetic behavior of ribozymes derived from two types of multiple-ribozyme expression vector were examined. In some cases, multiple ribozymes were expressed as a single RNA molecule and all the ribozymes were simply connected in tandem (connected type). In other cases, multiple ribozymes were flanked by cis-acting ribozymes at both their 5' and 3' ends so that, upon transcription, multiple ribozymes were trimmed at both their 5' and 3' ends, with resultant liberation of multiple independent ribozymes (shotgun type). When levels of ribozyme expression were examined for the shotgun-type vector, the level of the ribozyme transcript was found to be proportional to the number of units (n) connected in tandem. Accordingly, the activities of the shotgun-type ribozymes, in terms of the cleavage of HIV-1 RNA in vitro, were also found to be proportional to the number of units connected in tandem (n). By contrast, the activities of the connected-type ribozymes reached plateau values at around n = 3. These results indicate that, when the shotgun-type expression system is used, it is theoretically possible to generate various independent ribozymes, each specific for a different target site, without sacrificing the activity of any individual ribozyme.